Knowledge socialization and tax sanctions affecting compliance with mandatory reporting personal tax at KPP Surabaya Gubeng - Nofian Ismail Ismail (Enrichment : Journal of Management, 2023)
In this study there are three factors that can affect taxpayer compliance, namely tax knowledge, tax socialization and tax sanctions. The purpose of this study was to determine the effect of tax knowledge, tax socialization and tax sanctions on taxpayer compliance. The population in this study are taxpayers who are registered at KPP Pratama Gubeng Surabaya. This type of research is quantitative research. Data collection techniques using by distributing questionnaires to respondents. the sample in this study amounted to 100 respondents. The results showed that (1) Tax Knowledge had a positive and significant effect on Individual Taxpayer Compliance at KPP Surabaya Gubeng, (2) Tax Socialization had a positive and significant effect on Corporate Taxpayer Compliance at Surabaya Gubeng KPP, (3) Tax Sanctions had a positive effect and significant to Corporate Taxpayer Compliance at KPP Surabaya Gubeng.